Evaluación de las características fisicoquímicas, microbiológicas y sensoriales en una mermelada de fresa enriquecida con zapallo - Intriago Sarmiento, Bruno Alfredo (2023)
The objective of this research was to evaluate the physicochemical, microbiological and sensory characteristics of strawberry jam enriched with pumpkin. For this purpose, a DCA was carried out with three replications, whose ANOVA showed that the variables pH and ash presented significant statistical differences by means of Tukey's honestly significant test at 0.05, with treatment 1 presenting the best characteristics with values of 3.13 and 0.21% respectively, while for brix degrees no treatment complied with the minimum required, treatment 3 being the one that presented a higher value (58.8%). With respect to the nutritional content of vitamins A and C found in the jam, it was determined that it is a significant contribution and very useful for this type of product, especially in T1 and T3, where values higher than 50 ug/100 g of vitamin A and more than 2.35 mg/100 g of vitamin C were obtained. In the determination of microbiological analysis, all treatments were within the permissible limit for molds and yeasts <10 UP/cm3. Sensory analysis was performed with 75 untrained tasters, who could not find differences in the treatments for color, odor and flavor in the jam. It is concluded that strawberry and pumpkin are ideal for processing and use in jam production.